Optimization of extraction parameters of protein isolate from milk thistle seed: Physicochemical and functional characteristics - Ozgolet, Muhammed; Cakmak, Zeynep Hazal Tekin; Bozkurt, Fatih; Sagdic, Osman; Karasu, Salih (WILEY, 2024)
In the current study, optimization of milk thistle protein extraction parameters was carried out in terms of purity and yield. In addition, the characterization of proteins isolated from milk thistle seeds was conducted. The optimal conditions for achieving the highest purity of protein (MTP) from milk thistle seeds were identified as extraction pH 9.47, temperature 30 degrees C, and extraction time 180 min. Conversely, optimal values for overall protein yield (MTY) were determined at extraction pH 12, temperature 50 degrees C, and extraction time 167 min. The proteins obtained under these two sets of conditions (MTP and MTY) demonstrated comparable oil absorption capacity (OAC), foaming, and emulsifying capabilities, as well as stability, aligning with findings from previous studies on seed protein. Both proteins had the highest protein solubilities at pH 11. Both proteins' zeta potentials were closest to zero at pH 4, demonstrating their closeness to the isoelectric point. MTP and MTY had poorer antioxidant capabilities than the other protein isolates/concentrates. MTP and MTY contain high beta sheet concentrations that might enhance thermal stability and lower the digestibility of proteins. In conclusion, the protein extraction process demonstrated a high potential for achieving both substantial yield and remarkable purity with some decent technological and functional properties, thus holding promise for various applications in diverse fields. In our study, optimization of milk thistle protein extraction parameters was carried out in terms of purity and yield. Therefore, milk thistle proteins have a high potential for thermal stability and low digestion.image
Keywords: emulsifying properties; foaming capacity and stability; milk thistle seed; optimization of protein extraction; protein isolate; response surface; ENZYMATIC-HYDROLYSIS; ANTIOXIDANT ACTIVITY; FRACTIONATION; CONCENTRATE; WATERMELON; PEPTIDES; PRODUCTS; FLOUR; GUM; Food Science & Technology